49‐3L: Late‐News Paper: Flexible and Stretchable Hybrid Electronics Systems for Wearable Applications. Issue 1 (May 2016) - Yuan, Wei; Gu, Weibing; Lin, Jian; Cui, Zheng
Abstract : In this work, we report the use of printing strategy applied to the fabrication of flexible and stretchable circuit. The prepared Ag NWs paste was printed on glass substrate to form conductive circuit via screen printing, and liquid PDMS was casted on top of the printed Ag NWs circuit and cured to peel off the substrate. The randomly oriented Ag NWs were buried in PDMS to form conductive and stretchable circuit. We studied the influence of the diameter of Ag NWs on the surface morphology of Ag NWs/PDMS circuit during strain process and further analyzed the relationship between the surface micro‐structure and electrical property of Ag NWs/PDMS conductor. The results showed that the cracks happened on the surface of circuit with Ag NWs of smaller diameter in stretching process, while the buckling structure appeared after pre‐tension strain of 100% with Ag NWs of larger diameter. The buckling of Ag NWs/PDMS layer resulted in the stable resistance of stretchable circuit in the strain range of 0–50%. We also demonstrate the printed stretchable circuit integrated with LED array under bending, twisting and even stretching deformation. The printing method may provide a new step towards the development of stretchable strategies for conductive circuit and other wearable electronics.